A Rare Case of Orthokeratotic Hyperkeratosis in a Kid Induced by Malassezial Dermatitis - Sindhu,O.K; Vinu David,P; Hamza Palekkodan; Mary Grace,M; Neeraja,E; Athira P Nair; Ajith Jacob George (The Indian Veterinary Journal, 2024)
A two months old crossbred kid was presented with a complaint of alopecia and severe pruritus over the dorsal aspect of the body since one month. Ulcerative lesions were noted on the dorsal aspect of the neck and extensive moist pruritic lesions were observed  on lateral thigh and base of the tail. Cytological evaluation of skin impression revealed budding yeast cells suggestive of Malassezia spp.  along with bacterial (cocci) organisms . On histopathological examination, numerous budding yeasts were visible within the stratum corneal layer along with presence of orthokeratotic hyperkeratosis with acanthosis suggestiveof chronic skin irritation. The kid responded well to oral ketoconazole along with supportives like antihistaminics,  vitamin and mineral supplements.